Marine mammal populations and ocean noise : determining when noise causes biologically significant effects (National Academies Press, 2005)
"Attention has been drawn to the subject of how ocean noise affects marine mammals by a series of marine mammal strandings, lawsuits, and legislative hearings, and most recently, the report from the U.S. Commission on Ocean Policy. One way to assess the impact of ocean noise is to consider whether it causes changes in animal behavior that are "biologically significant," that is, those that affect an animal's ability to grow, survive, and reproduce. This report offers a conceptual model designed to clarify which marine mammal behaviors are biologically significant for conservation purposes. The report is intended to help scientists and policymakers interpret provisions of the federal Marine Mammal Protection Act."--Publisher's description